ANALISIS KESALAHAN SISWA KELAS VII SMP DAERAH DALAM MENYELESAIKAN SOAL CERITA PECAHAN - Edy Mulyono; Santi Irawati; Sudirman Sudirman (Jurnal Kajian Pembelajaran Matematika, 2021)
To Knowing student’s error is important for teachers to be able to develop learning. This research’s purpose is to describe the type student error in solving fraction problem. In this research, student gived three type problem.. The problem gived to 20 student at seven grade,it will be finish in 60 minute. According to the result will be choose 5 student to be subject of research. Colecting of data obtained from the result of test and interview. The result of test and interview will be analysis to find the type of student error according to Newman error analysis. The research result show that: (1) Reading error, S2 dan S4 misinterpreted sentences that exist on the matter. S2 wrote a known is to short and less meaningful. S2 didn’t write those asked in the question. (2) comprehension error, S2, S4 dan S5 didn’t understand each of question word. (3) transformation error, S2, S4 dan S5 can’t create a mathematical sentence of the existing problems. Subject can’t associate with known case in question. All of subject can’t make mathematical sentence in the application of algebra to solve problem. (4) process skill error, S1 can’t make an equation according to the problem, and make a mistake in multiplication of fraction (5) encoding error, S2, S4 dan S5 can find data that needed to solve the problem but student can’t write the corect answer.